Current trends in the synthesis of soluble and hot-melt polyimides - Kuleznev A. S.; Storozhuk I. P.; Zhukova V. A.; Zarubina A. N.; Ivankin A. N. (E3S Web of Conferences, 2023)
The work is devoted to a review of works published in recent years on the development of the chemical structure of soluble and hot-melt copolyimides, including a brief description of their synthesis and properties.